ANALISIS OPTIMASI JALUR DISTRIBUSI MENGGUNAKAN PENDEKATAN TSP (TRAVELING SALESMAN PROBLEM) UNTUK MENINGKATKAN EFISIENSI BIAYA DISTRIBUSI PADA TOKO UTHE GROSIR - Nasywa Shafa Azzahra; Najwa Nayra Aulia, Arista Binarsih, Paduloh (ADISAM PUBLISHER, 2024)
Uthe Grosir Store, a local company offering a variety of fresh fruits and other household needs, has seen an increase in consumer demand and branch expansion. However, this growth also impacts the increase in distribution costs. The main goal is to find a route with the shortest total distance. For this data analysis, the Traveling Salesman Problem (TSP) method is used, which is a method that aims to reduce distribution costs by finding the closest distance or route with the fastest time, and minimum distribution costsIn finding the shortest route, an algorithm is needed, and the algorithm used in this method is Branch and Bound. The researcher also uses QM For Windows software and conducts experiments to compare the results of manual calculations with the results of calculations using QM For Windows software. Based on the results and discussion, it is concluded that manual calculations provide optimal results, that is, route 1 (A → B → C → D → A) is the shortest route that can be taken with a distance of 56 kilometers.